THE EXPANDING EARTH DALAM PERSPEKTIF AL-QUR'AN - Nada Mohammad, Shafwatun; Ahmad Nurrohim; Aisyah, Septi (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
This study examines the relationship between the concept of the expansion of the earth from the perspective of the Qur'an and modern geological theory, especially regarding the movement of the earth's plates influenced by mantle convection. This study highlights the importance of understanding the expansion of the earth from both a scientific and spiritual perspective by analyzing terms in the Qur'an, such as madda, firasya, and daha. This study uses a qualitative approach through a literature study, integrating scientific literature and religious texts. The results of the study show that although there are differences between the concept of "expanding earth" in the Qur'an and modern scientific theory, both have a relationship that can be studied interdisciplinary. The discussion in this study emphasizes that the expansion of the earth does not only represent a physical phenomenon, but also reflects the greatness of Allah in the creation of the universe. The findings of this study are expected to enrich integrative scientific insights and provide new perspectives on the relationship between science and religion. In addition, the results of this study emphasize the relevance of religious values ​​in understanding geological phenomena and encourage constructive dialogue between science and spirituality